2010
DOI: 10.1073/pnas.0915056107
|View full text |Cite|
|
Sign up to set email alerts
|

Activation state and intracellular trafficking contribute to the repertoire of endogenous glycosphingolipids presented by CD1d

Abstract: The authors note that, due to a printer's error, on page 5054, right column, second paragraph, eighth line, "Within this clade, we estimated the mean age of the split between the ABC bears and the polar bears to be 152 ky, and the mean age for all polar bears as 134 ky, near the end of the Eemian interglacial period and completely in line with the stratigraphically determined age of the Poolepynten subfossil (11)," should instead appear as "Within this clade, we estimated the mean age of the split between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 42 publications
1
52
1
Order By: Relevance
“…An attractive possibility is that dyslipidemia in obesity modulates the loading of CD1d with accumulated self-lipids, a scenario supported by a number of studies that have investigated the response of iNKT cells to inflammatory stimuli (41,42,(45)(46)(47)(48)(49). Furthermore, dyslipidemia may also alter the levels of lipid binding/transfer proteins, such as apolipoprotein E, which has been shown to facilitate the delivery and presentation of glycolipids to iNKT cells (50).…”
Section: Discussionmentioning
confidence: 99%
“…An attractive possibility is that dyslipidemia in obesity modulates the loading of CD1d with accumulated self-lipids, a scenario supported by a number of studies that have investigated the response of iNKT cells to inflammatory stimuli (41,42,(45)(46)(47)(48)(49). Furthermore, dyslipidemia may also alter the levels of lipid binding/transfer proteins, such as apolipoprotein E, which has been shown to facilitate the delivery and presentation of glycolipids to iNKT cells (50).…”
Section: Discussionmentioning
confidence: 99%
“…Glycolipids were isolated from mucus by multiple rounds of chloroform-methanol extraction. Mucus was harvested as described above, and organic extraction of mucus was carried out according to the method of Muindi et al (41). Briefly, lipids were obtained by successive extractions with chloroform-methanol (1:1 followed by 1:2 [vol/vol]) and a final extraction with chloroform-methanol-water (4.8:3.5:1).…”
Section: Methodsmentioning
confidence: 99%
“…By vesicular and nonvesicular transport through the cell, β-GlcCer and other self-lipids might then access the endolysosomal compartment, where exposure to acidic hydrolases and lipid transfer proteins, such as GM2 activator (GM2a) and saposins, could orchestrate their loading onto recycling CD1d molecules. Cellular lipids bound to human CD1d molecules isolated from different cellular compartments have been determined by high-resolution mass spectrometry (39)(40)(41). Neo-synthesized CD1d molecules have been shown to acquire phosphatidylcholine in the ER, which is then exchanged for sphingomyelin when CD1d traffics through the Golgi (41).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in preliminary experiments we have observed that prosaposin enhances loading of β-GlcCer on plate-bound CD1d molecules at pH 7. Whether β-GlcCer could be identified as a major species associated with secreted or recycling CD1d molecules remains an open question, as the previous analysis was performed on resting Epstein-Barr virus-B cells (39,41) or in myeloid cells after digestion with ceramide glycanase, which does not cleave monohexoses from the ceramide backbone (40).…”
Section: Discussionmentioning
confidence: 99%